Skin ulcers infected with conditional pathogenic strains treated with local hydrogen water packing in two pemphigus vulgaris patients: Case reports with follow‐up for 2 months. Issue 5 (28th July 2019) - Yang, Fanping; Chen, Zihua; Chen, Sheng‐an; Zhu, Qinyuan; Wang, Lanting; Zhang, Wenhong; Luo, Xiaoqun
Abstract: We are the first to report on a new, safe, and effective treatment of infections induced by conditional pathogenic strains with local wet packing with hydrogen water. The new treatment method may also shed light on the therapy of chronic, inflammatory skin ulcers.